2018
DOI: 10.1186/s12885-018-4094-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of an active immunotherapy for asymptomatic phase Lymphoplasmacytic lymphoma with DNA vaccines encoding antigen-chemokine fusion: study protocol

Abstract: BackgroundThere is now a renewed interest in cancer vaccines. Patients responding to immune checkpoint blockade usually bear tumors that are heavily infiltrated by T cells and express a high load of neoantigens, indicating that the immune system is involved in the therapeutic effect of these agents; this finding strongly supports the use of cancer vaccine strategies. Lymphoplasmacytic lymphoma (LPL) is a low grade, incurable disease featuring an abnormal proliferation of Immunoglobulin (Ig)-producing malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…As an alternative, DNA vaccines could induce immune responses to the encoded antigens and are conceptually safer and more stable than conventional vaccines [11]. Recent advances in antigen designs and delivery methods have greatly enhanced the capacity and applications of DNA vaccines in infectious diseases, cancer, and allergies [12,13,14,15]. The potential clinical value of DNA vaccines for preventing and treating allergies is further highlighted by clinical trials that have demonstrated the safety and tolerability of DNA-based vaccines in patients with human infectious diseases and Japanese red cedar allergies [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, DNA vaccines could induce immune responses to the encoded antigens and are conceptually safer and more stable than conventional vaccines [11]. Recent advances in antigen designs and delivery methods have greatly enhanced the capacity and applications of DNA vaccines in infectious diseases, cancer, and allergies [12,13,14,15]. The potential clinical value of DNA vaccines for preventing and treating allergies is further highlighted by clinical trials that have demonstrated the safety and tolerability of DNA-based vaccines in patients with human infectious diseases and Japanese red cedar allergies [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In this type of vaccines, the antigen (Id) is expressed in vivo by transfected/infected cells, which could potentiate cellular immune responses, especially when these vectors are targeted to antigen presenting cells. This approach has been validated for B-cell lymphoma in a preclinical mouse model immunized with an adenovirus vector expressing A20 Id 6 and will be tested in clinical trials against B-cell lymphomas using DNA vaccines encoding patient-specific Ids linked to immunostimulatory sequences 29 , 30 . Regarding mRNA vaccines, the recent success of Covid-19 vaccines based on mRNAs expresing the spike protein of SARS-CoV-2, makes this approach very interesting for Id vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In current human DNA vaccination approaches antigen-encoding DNA vaccines are coadministered with soluble immunostimulatory agents which often have been approved for anti-tumor adjuvant therapy [ 105 ]. Besides, expression vectors that encode cytokines [ 106 ] or chemokines [ 107 ] are clinically tested. So far, DNA vaccines that integrate both the antigen expression unit and a molecular adjuvant into a single plasmid have been tested in a limited number of studies only.…”
Section: Optimization Of Dna Vaccinesmentioning
confidence: 99%